2017
DOI: 10.1159/000477606
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a Mango Fruit Powder Protects Mice from High-Fat Induced Insulin Resistance and Hepatic Fat Accumulation

Abstract: Background/Aims: The aim of this study was to gain more insight into the beneficial effects of mango fruit powder on the early metabolic adverse effects of a high-fat diet. Methods: The progressive dose-response effects of mango fruit powder on body composition, circulating parameters, and the expression of genes related to fatty acid oxidation and insulin sensitivity in key tissues were studied in mice fed a moderate (45%) high-fat diet. Results: Findings suggest that mango fruit powder exerts physiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…Obesity is also known to cause insulin resistance, which serves a key role in type 2 diabetes. Previous studies have indicated that in mice fed with HFD, an increase in fasting blood glucose and insulin levels was induced, while plant extracts were demonstrated to suppress the HFD-induced increase in these levels in obese animals (27)(28)(29). In the present study, the HFD also led to an increase in serum glucose and insulin levels and this increase in glucose and insulin levels were markedly decreased when mice fed with the HFD were administered dLE.…”
Section: Discussionsupporting
confidence: 61%
“…Obesity is also known to cause insulin resistance, which serves a key role in type 2 diabetes. Previous studies have indicated that in mice fed with HFD, an increase in fasting blood glucose and insulin levels was induced, while plant extracts were demonstrated to suppress the HFD-induced increase in these levels in obese animals (27)(28)(29). In the present study, the HFD also led to an increase in serum glucose and insulin levels and this increase in glucose and insulin levels were markedly decreased when mice fed with the HFD were administered dLE.…”
Section: Discussionsupporting
confidence: 61%
“…A previous study demonstrated acetic acid activates AMPKα, which in turn upregulates the expression of lipid oxidation genes in the liver to reduce fat accumulation [16]. Liver-specific AMPKα deletion in mice leads to increased plasma TG content and hepatic lipogenesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine lactadherin, free of lipid and protein contaminants, was purified and labeled with Alexa Fluor 647 or Alexa Fluor 488 [23, 24]. …”
Section: Methodsmentioning
confidence: 99%